Numerical thermal analysis of wall structure for sustainable buildings (2019)
Actuality. The last years the development of pre-urban areas around big European cities has intensified. The strict energy efficiency requirements force the developers to apply measures to ensure the high level of thermal protection in low-rise building. But in the same time business interest of the minimizing the initial costs of such buildings initiates the wide implementation of synthetic, non-recyclable or difficulty recyclable building materials for insulation, such as polystyrene insulation widely used, what is not sustainable taking into the consideration all life cycle of the building. The purpose. The main objective of the presented research is to define the eco-structures of recyclable organic based materials as the efficient industrial alternative to the modern insulation of low-rise buildings. Methodology. Engineering design has been applied to develop the structure solution and laboratory study has been realized to analyze the main physical and thermo-physical properties of the proposed structure. Finding. The wall structure for a sustainable building containing a wooden frame, a thermal insulation layer from materials of straw origin, an internal massive heat accumulation layer and an outer protective layer has been developed. Experiment of the thermo-technical properties study of the proposed structure element has been released in the big climate chamber TiR32 in the laboratory of building physics of Civil Engineering Faculty (STU in Bratislava). During the tests the following parameters have been evaluated: the temperatures in the external and internal surface of the test element in several points including on the joints (wood frame elements), where the thermal bridges were expected; overall thermal image of the external and internal wall in the extreme negative temperatures; thermal flow to the interior (during the first stage) – to define the coefficient of thermal conductibility of straw-wooden panel itself as well as the required long of heating periods and energy consumption to ensure temperature stability within thermic barrier integrated in the wall element. Scientific novelty and practical value. The received parameters are to implement for design of sustainable low-raised buildings structures of natural origin materials. The implementation of the proposed structure solution will facilitate balanced development of lo-raise building in EU.